Peran Guru Pendidikan Agama Katolik di Era Milenial dalam Meningkatkan Motivasi Belajar Peserta Didik - Meti, Nova (Vocat : Jurnal Pendidikan Katolik, 2023)
The problems found in this study are: 1) What is the Role of Catholic Religious Education in the Millennial Era in Increasing Student Learning Motivation? 2) What are the factors that influence student learning motivation? How are PAK teachers in this millennial era? From the existing problems, we can know that the purpose of this research is to find out the Role of Catholic Religious Education Teachers in the Millennial Era in increasing students' learning motivation. The research method used in this research is a qualitative research method with a descriptive approach. Learning motivation is an encouragement that comes from within students to gain knowledge and intelligence. Not only that, learning motivation can also provide changes in behavior and good achievements for students. Students who have high learning motivation will get good achievement. Learning motivation of students is influenced by internal and external factors. PAK teachers have an important role in increasing student learning motivation. In the millennial era, teachers are required to be digitally literate, use social media in the learning process, provide fun and meaningful learning, the teacher must be a role model, and also the teacher as a lifelong learner (long life education). The teacher's role in increasing student learning motivation is: making students active in teaching and learning activities, creating varied and innovative learning methods, increasing enthusiasm and enthusiasm for learning, giving awards/appreciations to students, holding competitions, giving punishments.